Speaking characters in Possessing the Secret of Joy - Sedehi, Kamelia Talebian; Talif, Rosli (Penerbit Universiti Kebangsaan Malaysia, 2014)
This paper is a study of Alice Walker’s Possessing the Secret of Joy in light of Julia Kristeva’s speaking subject. This novel deals with the issue of circumcision and its negative psychological effects on a woman’s mind. Moreover, it criticises female genital mutilation. In this novel, each character expresses his/her feelings, thoughts and emotions about female circumcision. In Julia Kristeva’s view, the speaking subject does not have a fixed identity but is in the process of being. The speaking subject's identity is shaped through using language and interaction with other people. This article applies Kristeva’s notion of the subject in process to Walker’s Possessing the Secret of Joy and primarily indicates Tashi’s opinion of circumcision. The findings of this study demonstrate that, through sisterhood, women can achieve their goal which is to abolish female circumcision. It indicates that although women are oppressed in African patriarchal societies, they can improve their life through sisterhood. It advises future female generations to stand up for their rights and reject the circumcision which hurts women physically and psychologically.